Complex anti-relapse therapy of various variants of the course of the vulvar lichen sclerosus: A randomized prospective study - Ekaterina V. Kolesnikova; Alexandr V. Zharov; Natalia V. Mingaleva; Milena Alexandrovna Penzhoyan (IP Berlin A.V., 2024)
Aim. To develop and evaluate the effectiveness of complex therapy of vulvar lichen sclerosus (VLS), considering the clinical and immunological variant (CIV) of the disease. Materials and methods. A randomized prospective study included 292 patients 20-70 years old with different CIVs of the VLS course: atrophic (n=101), sclerosing (n=154), scleroatrophic (n=37), as well as 35 females with VLS in the comparison group of the same age category. Based on the clinical, immunological, and morphological features of the VLS course, a complex anti-relapse therapy was developed, the effectiveness of which was evaluated after a year of follow-up in comparison with the standard of care (SoC) of patients (from the comparison group) based on the number of disease relapses and the results of the Vulvar Quality of Life Index Questionnaire (VQLI) survey of women with vulvar diseases. Results. In patients with the sclerosing variant of VLS, short courses of topical glucocorticoids during exacerbations are justified; in patients with the scleroatrophic variant - topical calcineurin inhibitors, in the atrophic variant - a protein-peptide complex from porcine blood leukocytes (vaginal suppositories and cream-balsam with lanolin) containing interleukin-1, 6, tumor necrosis factor α, transforming growth factor, macrophage migration inhibitory factor. Patients with any variant of VLS are instructed to follow household and hygienic recommendations, use emollients daily, take prophylactic doses of vitamins A, E, and D to correct its deficiency or insufficiency, as well as use local enzyme therapy, as indicated, aimed at preventing or treatment of cicatricial changes. Local estrogens were prescribed only to women with genitourinary menopausal syndrome in the peri- and postmenopausal period. The developed complex anti-relapse therapy of VLS showed greater clinical efficacy compared to SoC: 3.7-fold decrease in episodes of disease exacerbation, as well as a significant (p=0.001) 1.3-fold decrease in the negative effect of VLS on the QoL of patients in the main clinical group (15.4 points according to the VQLI assessment - a mild effect on QoL) compared to SoC with the average score of 27.6, which corresponded to a strong negative effect of the disease on QoL. Conclusion. The results of the study support the distinction of VLS CIVs and the need to consider their features when choosing an effective therapy for the disease. Properly selected complex, supportive therapy of VLS can significantly increase the QoL of patients, minimize the number of relapses, and prevent the development of complications, including, probably, the risk of malignant transformation.